A ideia de progresso na obra The Social Function of Science de John Desmond Bernal - Oliveira, Luís Henrique São João (2022)
This thesis focuses on the idea of progress developed by the British scientist and historian of science, John Desmond Bernal (1901-1971) in his work The Social Function of Science, published in 1939. In the first chapter, the thesis covers some definitions of progress for philosophy and how such views impact the understanding of the role of science. It also addresses ideas of progress in the History of Science that have become references. Finally, it presents the production of Bernal's work during a moment of strong social engagement of scientists identified with social issues and the anti-fascist struggle. The second chapter addresses the issue of fascism, mainly German, and the responses of some scientists about this landmark of social degeneration and science. Above all, Bernal's idea, and his defense of Nazism as a result of a decadent capitalism and its destructive impacts on the progress of science. The third chapter explores questions raised by Bernal about scientific work in democratic capitalist countries and its structural problems, as well as how it was done in the Soviet Union, defended as an example that is beginning to emerge. The chapter explores the contradictions of Bernal's arguments, which builds important analyzes and questions about doing science in capitalism, but when dealing with the Soviet model, it tries to build the idea of an infallible model. In this sense, we seek to understand the historiographical, but also political aspects of Bernal's proposal for progress